Venezuela as an example of resisting “colored” or “rose” revolutions - Denis Apolosov (Ибероамериканские тетради)
In our research, we aim to emphasize the importance of the decisions made by the government in functions as one to set up the Constituent National Assembly of Venezuela, or clarify the ideas of the national leader Nicolás Maduro, as, for example, his determination to rule out opposition parties. We will analyze how the President of the Republic managed to stop the process of insurrection and present the forecast of the actions to be undertaken by the opposition and the Venezuelan government.